Video Safety Brifing sebagai Salah Satu Strategi Komunikasi dalam Implementasi Program Kesehatan Keselamatan Kerja (K3) di Industri Pariwisata - Wina Puspita Sari; Asep Soegiarto (Universitas Majalengka, 2022)
The strategy implemented in communication planning begins with several steps (Wijaya, n.d.). The approach and method used in this research is descriptive qualitative. Data collection techniques with in-depth interviews and observation. The results of this study address strategic steps in communication planning including 1. Forming communicators. 2. Setting targets and analyzing audience needs. 3. Write a message. 4. Choose media and communication channels. Meanwhile, the communication channel intended for visitors is by using signs and a safety briefing video which will be broadcast on the website and on Cisaat Village's social media as well as on the social media of visitors or tourists. 5. Communication effect. The desired goal is a change in knowledge. An understanding of Occupational Safety and Health in the tourism industry is expected to change attitudes, become concerned and apply them in the form of behavior.